Glyphosate Sensor Based on Nanostructured Water-Gated CuO Field-Effect Transistor - Ogurcovs, Andrejs; Kadiwala, Kevon; Sledevskis, Eriks; Krasovska, Marina; Mizers, Valdis (MDPI, 2022)
This research presents a comparative analysis of water-gated thin film transistors based on a copper oxide (CuO) semiconductor in the form of a smooth film and a nanostructured surface. A smooth CuO film was deposited through reactive magnetron sputtering followed by annealing in atmosphere at a temperature of 280 (Formula presented.) C. Copper oxide nanostructures were obtained by hydrothermal synthesis on a preliminary magnetron sputtered 2 nm thick CuO precursor followed by annealing at 280 (Formula presented.) C. An X-ray diffraction (XRD) analysis of the samples revealed the presence of a tenorite (CuO) phase with a predominant orientation of (002). Scanning electron microscopy (SEM) and atomic force microscopy (AFM) studies of the samples revealed a highly developed surface with crystallites having a monoclinic syngony and dimensions of 15–20 nm in thickness, 150 nm in length, and 100 nm in height relative to a 2.5 nm height for the CuO crystallites of the smooth film. Electric measurements of the studied devices revealed typical current–voltage characteristics of semiconductors with predominant hole conductivity. The maximum ON/OFF ratio at a rain-source voltage of 0.4 volts and −1.2 volts on the gate for a smooth film was (Formula presented.), and for a nanostructured transistor, it was (Formula presented.). However, a much stronger saturation of the channel was observed for the nanostructured channel than for the smooth film. A test solution containing glyphosate dissolved in deionized water in three different concentrations of 5, 10, and 15 (Formula presented.) mol/L was used during the experiments. The principle of operation was based on the preliminary saturation of the solution with Cu ions, followed by the formation of a metal–organic complex alongside glyphate. The glyphosate contents in the analyte led to a decrease in the conductivity of the transistor on the axis of the smooth film. In turn, the opposite effect was observed on the nanostructured surface, i.e., an increase in conductivity was noted upon the introduction of an analyte. Despite this, the overall sensitivity of the nanostructured device was twice as high as that of the device with a thin film channel. The relative changes in the field-effect transistor (FET) conductivity at maximum glyphosate concentrations of 15 (Formula presented.) mol/L reached 19.42% for the nanostructured CuO film and 3.3% for the smooth film. © 2022 by the authors. --//-- This is an open access article Ogurcovs A, Kadiwala K, Sledevskis E, Krasovska M, Mizers V., "Glyphosate Sensor Based on Nanostructured Water-Gated CuO Field-Effect Transistor", Sensors (2022) 22(22):8744, doi: 10.3390/s22228744 published under the CC BY 4.0 licence.
Keywords: Research Subject Categories::NATURAL SCIENCES::Physics; copper oxide; glyphosate; nanostructures; thin-film transistor; water-gated field effect transistor